Association of Serum Vit D level with in-Hospital Outcome in Patients with Acute Myocardial Infarction - Noor Din, Ejaz Ul Haq, Muhammad Adeel, Rahidullah, Asadullah, Abdul Latif (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Low Vitamin D (Vit D) level is associated with disease severity amongst critical acute myocardial infarction (AMI) patients. This leads to the hypothesis that Vit D plays a role in the emergence of cardiac risk factors, contributing to worsening AMI patients’ short- and long-term prognoses. Therefore, there is still unclear data showing the potential impact of Vit D insufficiency or deficiency on the morbidity and mortality of AMI patients. So far, there has been no research conducted in Pakistan examining whether or not Vit D status are association to the outcome of hospitalization for coronary artery disease. Objective: The objective of the study is to examine the relationship between Vit D status on hospital admission and subsequent mortality and morbidity among patients with acute myocardial infarction. Study Design: Cross sectional observational study Study Setting: This study was conducted in the department of Interventional Cardiology, National Institute of Cardiovascular Diseases (NICVD), Karachi from Ist August 2022 to 31st January 2023. Methodology: Total 250 subjects were enrolled in the study and divided in to two groups. Group A with normal Vit D (30ng/ml or above) and Group B included lower Vit D level than 30ng/ml, all patients were suffering from AMI. Baseline demographic characteristics, including age, and gender (male/female), was recorded. The patients were tested for Vit D status and distributed in their respective groups. The history, complications, and clinical data were included. The stay in the hospital and any adverse outcomes that appeared during the stay were also recorded. The clinical results include HDL, TG, and troponin I of every patient were noted for the clinical correlation of AMI patients with adequate and deficiency of Vit D level. All the data was collected in the form of a questionnaire. The statistical analysis was done by using SPSS version 20. Results: Participants’ mean ages were 53.8 and 5.9 years old. Group A (patients with low Vit D status) averaged 59.6 years of age, whereas Group B (58.9 years) had normal Vit D status. The analysis showed a statistically non- significant (p>0.05) difference in average age between the groups. There were 250 patients, with male 43.6% and female 56.4%. Men (63.2%) and women (36.8%) were in Group A. There were 71.4% males and 28.6% females in Group B. We found out the 137(60.6%) significant adverse hospital outcomes (p<0.001) in Group B and had a more significant proportion of patients with diabetes mellitus and who had smoked (p = 0.002 and 0.001, respectively). In a multivariate logistic regression smoking, diabetes, Troponin I and low vitamin showed the significant risk association (p<0.001). Practical Implication: There is still a lack of conclusive evidence on the relationship between vitamin D insufficiency or deficiency and the morbidity and mortality of AMI patients. Until far, there has been no research in Pakistan linking serum vitamin D levels to in-hospital outcomes for patients suffering from acute myocardial infarction. Conclusion: The research shows an association between low Vit D status, adverse outcomes, and clinical parameters after AMI. A low blood Vit D level is independently associated to an increased risk of developing severe clinical outcomes during hospitalization, including death after an AMI. Keyword: Vit D, AMI, Vit D deficiency, low Vit D, Cardiovascular disease